Lobetyolin ameliorates DSS-induced ulcerative colitis in mice by alleviating inflammation, restoring barrier function, and modulating gut microbiota–metabolite interactions - Chang, Min; Liu, Fengping; Lu, Junhui; Wang, Qing; Liu, Jingwei; Chen, Xing (Frontiers in Microbiology, 2025)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease characterized by persistent mucosal inflammation in the colon, leading to substantial morbidity. Current therapies are often limited by side effects and relapse, emphasizing the need for safer, multi-target alternatives. This study investigated the protective effects and underlying mechanisms of lobetyolin (LBT), a natural polyacetylene glycoside, in a dextran sulfate sodium (DSS)-induced colitis mouse model. Male BALB/c mice were randomly divided into four groups: Control, DSS, and DSS treated with low (10 mg/kg) or high (50 mg/kg) doses of LBT. Clinical parameters were assessed using the disease activity index (DAI), histopathological staining, and biochemical assays. Inflammatory and oxidative stress markers were quantified by ELISA, tight junction proteins were analyzed by Western blotting and immunohistochemistry, gut microbiota composition was determined by 16S rRNA sequencing, and short-chain fatty acids (SCFAs) were measured by GC–MS. In addition, non-targeted metabolomics was performed using UHPLC–MS/MS. LBT treatment significantly alleviated DSS-induced colitis by improving body weight, colon length, and histological structure. It reduced TNF-α, IL-6, and IL-1β levels, restored antioxidant capacity (SOD, CAT, GSH), and enhanced epithelial barrier integrity (Occludin, Claudin-1, ZO-1). Moreover, LBT normalized gut microbial composition, increased SCFA production, and regulated amino sugar and nucleotide sugar metabolism. Collectively, these findings demonstrate that LBT exerts multi-target protective effects against UC by modulating inflammation, oxidative stress, epithelial barrier function, gut microbiota, and metabolic pathways.